PERSEPSI GURU IPA TERHADAP KURIKULUM 2013 DAN IMPLEMENTASINYA DI SMP se-KOTA PALU - Zainal, Syech (JSTT, 2015)
This study aimed to describe the perception of science teachers of curriculum 2013 and implementation in junior high school at the city of Palu. The method used in this research is descriptive qualitative method. The population is all science teachers as the city of Palu 150 people and purposive sampling technique is sampling the number of respondents 65 teachers targeted curriculum implementation 2013. The results of the perception of science teachers classified curriculum criteria. Teachers' perceptions of the implementation of the criteria classified underprivileged. Factors supporting and implementing the curriculum 2013 is the role of the school principal, the creativity of teachers, learners activity, socialization, facilities and learning resources, as well as a conducive environment. Solutions to optimize the implementation of the curriculum in 2013 is the teacher should instill self-dicipline to learners, providing textbooks and books student teacher, discussion with peers, maximizing the school environment as an alternative source of student learning and optimization of exercising socialization, mentoring, coaching and clinical teachers.